Targeted antibiotic treatment of lame sheep with footrot using either oxytetracycline or gamithromycin. (11th January 2014) - Strobel, H.; Lauseker, M.; Forbes, A. B.
Abstract : A study on parenteral antibiotic treatment in sheep footrot was conducted on 10 farms in southern Germany to obtain information on the efficacy of gamithromycin under practical use conditions compared with a positive control. On each farm, 20 (10 on one farm) lame sheep were clinically evaluated and divided into two groups. On day 1, sheep were treated once according to group with either long‐acting oxytetracycline (OTC) at 20 mg/kg bodyweight or gamithromycin at 6 mg/kg; clinical responses were assessed 21 days later. When compared with day 1, both treatments reduced clinical lameness, as reflected in the reduction in the number of footrot‐affected feet (OTC: 79.3 per cent; gamithromycin: 93.7 per cent) and in the severity of the lesions. The difference between the two treatments was significant (P<0.01) with an OR of 6.1 in favour of gamithromycin. Of the 33 sheep that were still lame on day 21, nine mildly affected animals were not re‐treated and the remaining 24 sheep were re‐treated with gamithromycin. On day 42, all but two (on the same farm) of the 33 sheep were cured, giving an overall response rate in this study to one or two parenteral antibiotic treatments of 99 per cent.